Cost of Producing Fresh Market Grapefruit in Indian River in 2018/19 - Ariel Singerman (EDIS)
This 4-page fact sheet written by Ariel Singerman and published by the UF/IFAS Food and Resource Economics Department presents the cost of production per acre for growing fresh grapefruit in the Indian River region during 2018/19. Estimates reflect costs and cultural practices for a panel of growers, particularly important information at this time because, since citrus greening (HLB) was found, growers have been modifying their practices from year to year in an attempt to cope with the disease. https://edis.ifas.ufl.edu/fe1078